Development of a Web-Based Administration System for the Bantu Sodara Community Using the Waterfall Method - Bima Randy Gumilang; Agung Nugroho; Ahmad Turmudi Zy (University of Respati Yogyakarta, Indonesia, 2024)
In this research, the aim is to develop a web-based administrative system for the Bantu Sodara Community to overcome manual administration constraints. Through a web-based system development approach, needs analysis, system design, implementation, and evaluation were conducted. Data were obtained through interviews, observations, and literature reviews. The results indicate that the development of a web-based administrative system can improve the efficiency and accuracy of community administration data management. The implementation of this system provides ease of access, centralized data management, and transparency of information for all community members. Thus, the use of a web-based administrative system is expected to provide an effective solution to the manual administration constraints experienced by the Bantu Sodara Community.This research aims to develop a web-based administrative system for the Bantu Sodara Community to address the limitations of manual administration. The system development process included needs analysis, system design, implementation, and evaluation. Data were collected through interviews, observations, and literature reviews. The results indicate that the web-based administrative system significantly improves the efficiency and accuracy of community data management. The system enhances accessibility, centralizes data management, and ensures transparency of information for all community members. Therefore, the implementation of this web-based system is an effective solution to the administrative challenges faced by the Bantu Sodara Community.